On The Role Of The Service Sector In The Republic Of Uzbekistan - Salikhova Alina Muratovna; Hamdamova Zukhra uthor (Journal of Artificial Intelligence and Digital Economy, 2024)
This study is dedicated to examining the role of the service sector in the economy of the Republic of Uzbekistan. It analyzes the key aspects of development and the impact of the service sector within the context of modern economic trends in the country. Special attention is given to the influence of the service sector on the socio-economic development of Uzbekistan, identifying problems and prospects for the development of this sector. The research aims to identify the key factors contributing to the effective development of the service sector, as well as defining strategic directions for the sector's development in the context of current challenges and opportunities.